Application of Taguchi Method for Optimizing of Mechanical Properties of Polystyrene-Carbon Nanotube Nanocomposite. Issue 2 (February 2017) - Farbodi, Maryam
Carbon nanotube (CNT) was selected as reinforcement agent to improve the mechanical properties of polystyrene (PS). PS–CNT nanocomposite was prepared by mixing CNT with a solution of PS. Taguchi experimental design method was used to determine the optimal conditions for preparation of the nanocomposite. The effects of six factors including the type of CNT (A), type of solvent (B), type of PS (C), drying temperature of nanocomposite film (D), the percentage of CNT (E) and duration of mixing after adding CNT (F) were investigated at different levels. The tensile strength values of PS-CNT nanocomposite films were used as the responses for the analysis of data using signal to noise (S/N) method. Using this method, the optimum conditions were obtained as: the type of CNT: functionalized single walled CNT (SWCNT), the percentage of SWCNT: 1.5%, the type of solution: tetrahydrofuran, the type of PS: GPPS 1460, drying temperature: 25 °C, duration of mixing: 1 hour. Based on the obtained values, the order of the effect of factors was CEADBF. The most effective and the least effective factors were C and F, respectively. The calculated F-ratio of each factor showed that at 95% confidence interval, the F values for all factors except factor F have significant effects on the response values. Also, the functionalization of the CNTs surfaces by –OH and –COOH groups confirmed by FTIR and SEM techniques.